2020
DOI: 10.1210/endocr/bqaa128
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Ovarian Hormones in the Modulation of Sleep in Females Across the Adult Lifespan

Abstract: Ovarian hormones, including 17β-estradiol, are implicated in numerous physiological processes, including sleep. Beginning at puberty, girls report more sleep complaints than boys, which is maintained throughout the reproductive life stage. Sleep problems are exacerbated during the menopausal transition, evidenced by greater risk for sleep disorders. There is emerging evidence that menopause-associated hormone loss contributes to this elevated risk, but age is also an important factor. The extent to which menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 189 publications
0
31
1
2
Order By: Relevance
“…In addition to the contributions of biological aging, menopause-related insomnia, persisting in postmenopausal states, might partly account for the remarkable decline of sleep quality in females. There is some evidence 54 56 that menopausal and postmenopausal women frequently report sleep complaints, including nighttime awakening with difficulty falling back asleep, possibly linked with characteristic concomitant menopause symptoms (e.g., vasomotor symptoms such as hot flashes and night sweats, or mood swings) mediated by rapid changes in the ovarian hormonal milieu. This is apparently related with the higher prevalence of insomnia during menopause and postmenopause 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the contributions of biological aging, menopause-related insomnia, persisting in postmenopausal states, might partly account for the remarkable decline of sleep quality in females. There is some evidence 54 56 that menopausal and postmenopausal women frequently report sleep complaints, including nighttime awakening with difficulty falling back asleep, possibly linked with characteristic concomitant menopause symptoms (e.g., vasomotor symptoms such as hot flashes and night sweats, or mood swings) mediated by rapid changes in the ovarian hormonal milieu. This is apparently related with the higher prevalence of insomnia during menopause and postmenopause 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The associations between that day’s sedentary time and that night’s WASO and awakenings were only found in the analyses that included all the participants. Peri- and post-menopausal status are associated with a higher prevalence of sleep disorders, sleep fragmentation, and hot flashes resulting in a greater number of awakenings [ 29 ]. These changes may account for the different findings in the analyses conducted in the full versus female-specific sample.…”
Section: Discussionmentioning
confidence: 99%
“…E2 is a form of estrogens which is implicated in numerous physiological processes ( 39 ). Studies have reported that E2 is implicated in cognitive function, mood regulation, learning, memory, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that E2 is implicated in cognitive function, mood regulation, learning, memory, etc. ( 39 , 40 ). In addition, E2 plays a critical role in neurodegenerative diseases including Alzheimer’s disease, dementia and stroke ( 41 ).…”
Section: Discussionmentioning
confidence: 99%